Evaluation of Blood Glucose Response after Consumption of Food and Extracts from Field Crops in University Students - Al-Mousawi, Hakeem; Hatim, Sajdeen; Albalawi, Sabaa; Almansarawi, Ali; Razzaq, Anfal; Al-Salhi, Ahmed (Health & Medical Sciences, 2025)
This study examined the glycemic response of healthy university students after consuming rice, bulgur, and extracts of fenugreek, cinnamon, and coriander. Blood glucose was measured at seven time points: baseline (0 minutes) and at 20, 40, 60, 80, 100, and 120 minutes. The research was conducted on five groups of students, each receiving one of the test foods or extracts in standardized amounts (300 g of rice or bulgur and 300 ml of each extract). At the same time, all participants remained seated and inactive during monitoring to ensure controlled experimental conditions. The findings showed distinct differences among the tested substances, reflecting their varying nutritional and metabolic characteristics. Rice produced the most significant rise in blood glucose, especially between 20 and 40 minutes, consistent with its high glycemic index and rapid starch digestion. Bulgur demonstrated a slower, more moderate increase, with glucose levels rising gradually and then declining steadily from minute 80, due to its fiber content and coarse grain structure, which slows absorption. The plant extracts showed markedly lower responses than the starchy foods. Fenugreek extract produced the lowest rise, maintaining minimal changes over 120 minutes due to its viscous fibers and insulin-enhancing compounds. Cinnamon extract generated a moderate peak and approached baseline values between 100 and 120 minutes, while coriander extract showed a low, stable response with no sharp increases. Overall, the results demonstrate that the type of consumed substance strongly shapes postprandial glycemic behavior, with whole grains and plant extracts promoting a more stable and less pronounced response than refined starchy foods.